2010
DOI: 10.1152/jn.00034.2010
|View full text |Cite
|
Sign up to set email alerts
|

Gain of Function in FHM-1 Cav2.1 Knock-In Mice Is Related to the Shape of the Action Potential

Abstract: González Inchauspe C, Urbano FJ, Di Guilmi MN, Forsythe ID, Ferrari MD, van den Maagdenberg AMJM, Uchitel OD. Gain of function in FHM-1 Ca v 2.1 knock-in mice is related to the shape of the action potential. J Neurophysiol 104: 291-299, 2010. First published May 19, 2010 doi:10.1152/jn.00034.2010. Familial hemiplegic migraine type-1 FHM-1 is caused by missense mutations in the CACNA1A gene that encodes the ␣ 1A pore-forming subunit of Ca V 2.1 Ca 2ϩ channels. We used knock-in (KI) transgenic mice harboring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 29 publications
3
42
1
Order By: Relevance
“…Assuming presynaptic Ca 2+ currents through Ca v 2.1 channels can be modeled by Hodgkin-Huxley equations, a shift to more negative activation voltages by the FHM-1 mutations (24) theoretically could generate larger Ca 2+ currents during APs (38); however, it was recently shown that, during short 1-ms APs elicited at the calyx of Held in R192Q mice, a hyperpolarizing shift in the activation voltage by the R192Q mutation was insufficient to alter presynaptic Ca 2+ influx. Only when the AP duration was prolonged by 1 to 2 ms was the shift in the activation by the R192Q mutation sufficient to cause greater presynaptic Ca 2+ influx (39). Importantly, the AP duration at PF terminals closely resembles the normal, 1-ms APs at the calyx of Held (40, 41), .…”
Section: Fhm-1 Mutant P/q-type Channels Appear To Be In a Basally Facmentioning
confidence: 93%
“…Assuming presynaptic Ca 2+ currents through Ca v 2.1 channels can be modeled by Hodgkin-Huxley equations, a shift to more negative activation voltages by the FHM-1 mutations (24) theoretically could generate larger Ca 2+ currents during APs (38); however, it was recently shown that, during short 1-ms APs elicited at the calyx of Held in R192Q mice, a hyperpolarizing shift in the activation voltage by the R192Q mutation was insufficient to alter presynaptic Ca 2+ influx. Only when the AP duration was prolonged by 1 to 2 ms was the shift in the activation by the R192Q mutation sufficient to cause greater presynaptic Ca 2+ influx (39). Importantly, the AP duration at PF terminals closely resembles the normal, 1-ms APs at the calyx of Held (40, 41), .…”
Section: Fhm-1 Mutant P/q-type Channels Appear To Be In a Basally Facmentioning
confidence: 93%
“…4,5 Knockin (KI) mice carrying FHM1 mutations show increased P/Q-type Ca 2+ current density in central neurons including cortical pyramidal cells. 1,[6][7][8] Interestingly, the FHM1 KI mice also show a reduced threshold for induction of cortical spreading depression (CSD) and an increased velocity of propagation of CSD. 1,6,8 CSD can be induced in animals by focal stimulation of the cerebral cortex and consists in a slowly propagating wave of cortical neuronal and glial depolarization, whose mechanisms remain unclear and controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, while in cortical pyramidal cells of R192Q KI mice the shift to lower voltages of Ca v 2.1 channel activation resulted in increased AP-evoked Ca current, a similar shift of mutant R192Q channels at the Calyx of Held synaptic terminals did not alter the AP-evoked Ca current (Inchauspe et al 2010). The different durations of the AP in pyramidal cells and Calyx (1.8 vs 0.44 ms AP half width) may largely explain the differential effects of the FHM1 mutation on the AP-evoked Ca current; in fact, the AP-evoked Ca current became larger in knockin compared to WT Calyx terminals when the longer duration pyramidal cell AP was used as depolarizing stimulus (Inchauspe et al 2010).…”
Section: Effect Of Fhm1 Mutations On the Biophysicalmentioning
confidence: 92%
“…The analysis of the P/Q-type calcium current in different neurons (including cortical and TG neurons) of R192Q and S218L FHM1 knockin mice revealed gain-offunction of the Ca v 2.1 current in a wide range of relatively mild depolarizations, reflecting shifted activation of mutant Ca v 2.1 channels to more negative voltages (van den Tottene et al 2009;Inchauspe et al 2010;Fioretti et al 2011Gao et al 2012. P/Q current densities were similar in knockin and wild-type (WT) neurons at higher voltages (that elicit maximal Ca v 2.1 channel open probability), indicating similar densities of functional Ca v 2.1 channels (van den Tottene et al 2009;Fioretti et al 2011;Gao et al 2012).…”
Section: Effect Of Fhm1 Mutations On the Biophysicalmentioning
confidence: 99%
See 1 more Smart Citation